Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2500/ajra.2015.29.4125
|View full text |Cite
|
Sign up to set email alerts
|

Squeeze Bottle versus Saline Spray after Endoscopic Sinus Surgery for Chronic Rhinosinusitis: A Pilot Multicentre Trial

Abstract: In this pilot multicenter trial examining patients with chronic rhinosinusitis undergoing ESS, both squeeze bottle and saline spray showed significant improvement in SNOT-22, POSE, and NSS scores at one-month postoperatively. Because the study was nonpowered, we cannot rule out a potential difference between the two treatment groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…However, the effect had diminished at 12 weeks postoperatively 28 . The other (86 patients) found no significant difference between groups 29 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, the effect had diminished at 12 weeks postoperatively 28 . The other (86 patients) found no significant difference between groups 29 …”
Section: Discussionmentioning
confidence: 82%
“…28 The other (86 patients) found no significant difference between groups. 29 Furthermore, one randomized control study compared corticoste- found that douching was significantly more effective in penetrating the maxillary sinus (P = .036) and frontal recess (P = .003). 32 We found that the high-volume devices were most effective in Although randomized controlled trials have yielded conflicting results, we found that high-volume devices yielded higher symptom scores from patients with all types of rhinosinusitis and resulted in minimal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous randomized studies have evaluated the use of saline in the endoscopic sinus surgery population; however, data are scarce in the EEA population. 6 Furthermore, a survey study examined practice patterns of CPAP use in various endoscopic and nonendoscopic nasal surgeries and found that although the majority of surgeons stop CPAP use for 1 to 2 weeks postoperatively, some do not, with seemingly few complications. 7 A recent survey study likewise found highly variable practice patterns among respondents with respect to skull base surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4 Saline nasal treatment increases hydration in the sol layer and enhances mucociliary function. 4 For greater clearance, nasal irrigation with large volume and high pressure saline is effective on mechanical removal of postoperative clotted blood, debris, and crust, 5,6 and the risk of postoperative adhesions is minimized and ostiomeatal patency is promoted. When thick eosinophilic mucin is effectively removed, chronic inflammation can be brought under control.…”
Section: Introductionmentioning
confidence: 99%